James M. Decker’s forced thought of an end to ideology in George Orwell’s 1984 - Khmiri, Dr. Mariem (International Journal of Humanities and Education Development (IJHED), 2021)
James M. Decker examines 1984 under a skeptical lens as a statement in favor of capitalist democracy: which according to him thrusts Orwell forthright in the mist of ideology. A more compelling question, however, would be: Why was the interpretation of Orwell’s 1984 mostly a trudge against one particular version of totalitarianism called Stalinism? Isn’t it a form of complicity to always ground totalitarianism in Stalinism (thus also masking the totalitarianism exerted elsewhere in the world)? It seems it is not the Inner Party employing ideology to keep the masses under control as much as James M. Decker who provides an entrance into 1984 within a paradigm which excludes any possibility of meaning outside his apocalyptic landscape of a humanity not less thoughtless than out of history.